Cyber Bullying and Its Relationship with The Psychological Unity among The Students of College of Education at Umm Al-Qura University - Basyouni, Sawzan Sadaqa; Alharbi, Malak Ali (Journal of Educational and Psychological Sciences, 2020)
The current study aimed to know the level of the phenomenon of cyber bullying among university students، and the relationship between practicing this behavior "cyber bullying" and psychological loneliness. The researchers applied the cyber bullying scale to find out the level of this phenomenon among the students. Also، they applied the measure of psychological loneliness to determine the level of the feeling of psychological loneliness among the students. The sample of the study consisted of (133) female students of the College of Education at Umm Al-Qura University، included all College specialties and all levels of study during the first semester of the academic year 1440 AH. The results of the study showed that the mean averages of all expressions of the cyber bullying scale ranged between (medium and high). This means that the terms of the scale illustrate the reality of female students in practicing the behaviors that express cyber bullying. The mean averages of all expressions of the psychological loneliness scale were medium، which indicate that the sample members also suffer from psychological loneliness. The results also showed a statistically significant correlation between the psychological loneliness and the behavior of cyber bullying at 0.05 level.